2010
DOI: 10.1093/bioinformatics/btq194
|View full text |Cite
|
Sign up to set email alerts
|

A spectral graph theoretic approach to quantification and calibration of collective morphological differences in cell images

Abstract: Motivation: High-throughput image-based assay technologies can rapidly produce a large number of cell images for drug screening, but data analysis is still a major bottleneck that limits their utility. Quantifying a wide variety of morphological differences observed in cell images under different drug influences is still a challenging task because the result can be highly sensitive to sampling and noise.Results: We propose a graph-based approach to cell image analysis. We define graph transition energy to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The characterisation of mitochondrial volume and morphology is thus easily biassed and dependent on the experience of the experimenter. Recently however, elaborate computational analysis of mitochondrial structures has shown that mitochondrial networks can in principle be described in numerical terms ( Lin et al, 2010; Peng et al, 2011; Sukhorukov et al, 2012 ). If easily available, such metrics would thus reduce the subjectivity in assessing mitochondrial morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…The characterisation of mitochondrial volume and morphology is thus easily biassed and dependent on the experience of the experimenter. Recently however, elaborate computational analysis of mitochondrial structures has shown that mitochondrial networks can in principle be described in numerical terms ( Lin et al, 2010; Peng et al, 2011; Sukhorukov et al, 2012 ). If easily available, such metrics would thus reduce the subjectivity in assessing mitochondrial morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we compared the method to that proposed in (Lin et al., ) for quantifying mitochondrial fragmentation from images of single cells. Their method uses a different set of features, and the fragmentation is quantified using weighted 6‐nearest neighbour regression.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted score for the nonfragmented mitochondria is overestimated, and the predicted score for the fragmented mitochondria is underestimated; however, this bias is least apparent in the case of MT + TF. Next, we compared the method to that proposed in (Lin et al, 2010) for quantifying mitochondrial fragmentation from images of single cells. Their method uses a different set of features, and the fragmentation is quantified using weighted 6-nearest neighbour regression.…”
Section: Validation Of the Regression Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The main idea is that we quantify the amount of information between particles according to their graph energy 18 . Our goal is to transform the kernel space so that the distance in the transformed space correlated with the difference of the labels of particles.…”
Section: Methods Deductionmentioning
confidence: 99%